An allozyme polymorphism is associated with a large chromosomal inversion in the marine snail Littorina fabalis. (26th June 2022) - Le Moan, Alan; Panova, Marina; De Jode, Aurélien; Ortega‐Martinez, Olga; Duvetorp, Mårten; Faria, Rui; Butlin, Roger; Johannesson, Kerstin
Abstract: Understanding the genetic targets of natural selection is one of the most challenging goals of population genetics. Some of the earliest candidate genes were identified from associations between allozyme allele frequencies and environmental variation. One such example is the clinal polymorphism in the arginine kinase ( Ak ) gene in the marine snail Littorina fabalis . While other enzyme loci do not show differences in allozyme frequencies among populations, the Ak alleles are near differential fixation across repeated wave exposure gradients in Europe. Here, we use this case to illustrate how a new sequencing toolbox can be employed to characterize the genomic architecture associated with historical candidate genes. We found that the Ak alleles differ by nine nonsynonymous substitutions, which perfectly explain the different migration patterns of the allozymes during electrophoresis. Moreover, by exploring the genomic context of the Ak gene, we found that the three main Ak alleles are located on different arrangements of a putative chromosomal inversion that reaches near fixation at the opposing ends of two transects covering a wave exposure gradient. This shows Ak is part of a large (3/4 of the chromosome) genomic block of differentiation, in which Ak is unlikely to be the only target of divergent selection. Nevertheless, the nonsynonymous substitutions among Ak alleles and the complete association of one allele with one inversion arrangement suggest that the Ak gene is a strong candidate to contribute to the adaptive significance of the inversion.